Hornets and Yellowjackets, Vespula and Dolichovespula spp. - E. E. Grissell (EDIS)
Only two of the 16 Nearctic species of Vespula are known from Florida (Miller 1961). These are the two yellowjackets: V. maculifrons (Buysson) and V. squamosa (Drury). One species of Dolichovespula is also present: the baldfaced hornet, D. maculata (Linnaeus). The baldfaced hornet is actually a yellowjacket. It receives its common name of baldfaced from its largely black color but mostly white face, and that of hornet because of its large size and aerial nest. In general, the term "hornet" is used for species which nest above ground and the term "yellowjacket" for those which make subterranean nests. All species are social, living in colonies of hundreds to thousands of individuals. These wasps are adept at stinging and are especially aroused if danger threatens the nest. Unlike the honeybee, which dies upon inflicting a single sting, vespine wasps may sting as often as they find a target. This document is EENY-081 (originally published as DPI Entomology Circular No. 142), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 1999.